The Impact of Unmet Healthcare Needs on the Perceived Health Status of Older Europeans During COVID-19 - Šime Smolić; Nikola Blaževski; Margareta Fabijančić (Frontiers Media S.A., 2024)
ObjectivesTo examine how unmet healthcare needs and the exposure to the pandemic impacted self-reported health (SRH) among individuals aged 50 and above.MethodsWe use data from two waves of the Survey of Health, Ageing and Retirement in Europe (SHARE) Corona Survey collected in 2020 and 2021 in 27 European countries and Israel (N = 42,854). Three dimensions of barriers to healthcare access were investigated: healthcare forgone, postponed, and denied. Mixed-effects logistic regression analysis was employed to explore SRH deterioration during the pandemic.ResultsFindings indicate that unmet healthcare needs decreased throughout the pandemic but significantly contributed to the worsening of SRH among older adults. Mild or severe exposure to the pandemic heightened the likelihood of reporting deteriorated SRH. Additionally, the pandemic disproportionately affected females, the oldest-old, and those living alone or facing economic vulnerability.ConclusionTo mitigate the adverse effects on the health status of older adults, policymakers are strongly advised to prioritize addressing the healthcare needs of those who have been disproportionately affected by the pandemic.